O planejamento como base de uma moderna gestão pública - Barreto, Paulo Ricardo Ceni (2004)
This report presents an analysis of the planning process developed by the Executive Power of fifteen small towns from the northwest of the state of Rio Grande do Sul, a region under the responsibility of Serviço Regional de Santo Ângelo, which is section of Tribunal de Contas do Estado. The study, both exploratory and descriptive, displays the historical context, searching for the reasons that led to the development of the public administration in the world and the main cultural currents involved in the changes. It also presents the legal aspects and the historical evolution of planning in Brazil and its tools. A need for an alternative planning was identified, in terms of amplitude in space and time and commitment to its own process, and finally, the results achieved are shown, promoting an analysis of context and of the main difficulties, faced by the small towns, of organizing their planning, in a way that is adequate to the current demands of governmental organizations and society. By means of data analysis, it was found out that most of small towns don’t use their budgets as a planning tool, instead, they only use it for meeting the legal demands and, in some cases, not even for this. Also, it was found out that there is no strategic planning at all.